Effects of compound fermentation with Limosilactobacillus fermentum HHL-5 and citric acid on wilted king grass silage - Dou, Ying; Xu, Xindan; Chen, Rong; Yang, Jinsong; Liu, Wei; Tan, Haisheng (Frontiers in Veterinary Science, 2025)
To improve the silage quality of wilted king grass, the study investigated the effects of Limosilactobacillus fermentum HHL-5 alone and L. fermentum complex citric acid fermentation on wilted king grass silage. Four experimental groups were designed as follows: no additive (CK), citric acid addition (CA), L. fermentum addition (L), and combined L. fermentum and citric acid addition (LCA). The fermentation quality, microbial composition, and aerobic stability of the silage in each group were analyzed. After 30 days of ensiling, LCA had the highest protein content, and L had the lowest ADF content (p < 0.05). Lactic acid and acetic acid contents were significantly increased in the LCA group (p < 0.05), whereas lactic acid content was increased and acetic acid content was significantly decreased in the L group (p < 0.05). Ammonia nitrogen content was significantly decreased in the CA and LCA groups (p < 0.05). The L group was not significantly different from the CK group in terms of bacterial diversity and relative abundance, whereas the LCA group showed markedly higher bacterial diversity and was considerably different from the CK group. The relative abundance of Lactobacillus in the LCA group was higher than that in the L group, while that of Enterobacterales was lower. Compared to the addition of L. fermentum alone, complex citric acid silage significantly enhanced the aerobic stability of this feed. In summary, the application of L. fermentum combined with citric acid can more effectively improve the quality of wilted king grass silage.